COMMUNITY BASED TOURISM SEBAGAI SUATU ALTERNATIF DALAM MENINGKATKAN KESEJAHTERAAN PETANI (STUDI KASUS: DESA BUDAYA KERTALANGU KOTA DENPASAR) - Luh Putu Kirana Pratiwi; Ni Putu Pandawani; Putu Eka Pasmidi Ariati (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2017)
The aims of this study are analyzing the influence of tourism potential on the empowerment of farmers, the effect of farmers empowerment on farmer participation, and the influence of farmers participation on improving the welfare of farmers. The study is done at farmers in Subak Padanggalak, Kertalangu Culture Village. The sample done with purposive sampling which consisted of 57 people. Technique analysis data using Partial Least Square (PLS) with Smart PLS program. The research results show that tourism potential has significant impact on farmers empowerment, and it has followed by farmers empowerment also have significant impact on the farmer participation. But, to the farmers participation have not significant on increasing the farmers welfare. This indicate that, the farmer participation have yet to opimal benefit in supporting welfare their life. Farmer have yet to look as the tourism subject. The role of farmers and subak limited to support the development tourism, which the farmers have yet involvement directly. It suggested of effort community based tourism, the need for support private sector to develop agriculture to agrotourism. Trough the development of agrotourism a lot of commodities agriculture can be developed, and been undertaken by various manufacturing agriculture products that have value to. The government through of relevant agencies are expected to provide access capital and market acces as well as various guidance in managing agricultural products as a product tourism, so that farmer as the subject tourism having competitiveness high in increase skill and produce impact on improving well-being farmers.